The relationship between internet use preference and loneliness among college students during COVID-19: The chain mediating effect of online social support and self-esteem - Luo, Qing; Huang, Lu; Wu, Na (Frontiers in Psychology, 2022)
Since the outbreak of COVID-19, the Internet has become an increasingly prominent factor in areas of study and life for college students. While various Internet functions have met a range of needs for these individuals, such use has also impacted their mental health. Under the framework of Ecological System Theory and the context of COVID-19, this study constructed a chain mediation model based on questionnaire survey data from 1053 college students (685 women and 368 men, aged 19.46 ± 1.53 years), with the aim of clarifying the mechanism between Internet use preference and loneliness. We found that Internet use preference not only positively predicted loneliness but also indirectly influenced loneliness through the mediators of online social support and self-esteem, thereby impacting loneliness through the “online social support → self-esteem” chain. The advent of COVID-19 has impacted people’s lifestyles and has changed the impact of the Internet on individual mental health. This study provides a new way to further understand college students’ Internet use preferences, online social support, self-esteem, and loneliness status during COVID-19. It provides targeted interventions for college students’ loneliness during COVID-19. The results also indicate the need to pay attention to college students’ mental health status during COVID-19.